Analysis of iceberg-tsunamis from large-scale experiments - ATTILI, TOMMASO (Pisa University, 2019)
Large impulse waves are generated by the calving of icebergs in oceans, bays or lakes. These waves are called iceberg-tsunamis. Iceberg-tsunamis are particularly relevant in Greenland and Antarctic during the summer season. An iceberg-tsunami reaching an amplitude of approximately 50 m was observed at the Eqip Sermia glacier in 2014 and several smaller events recently occurred in Greenland, Patagonia and New Zealand, where in some cases harbours and boats were destroyed. The forecasting of the relevant wave features, e.g. the maximum wave height, plays a key role for hazard assessment and the mitigation of iceberg-tsunamis. The present study focuses on iceberg-tsunami generation and propagation by analysing the experimental data of Heller (2019) and Heller et al. (2019). This included the analysis of large-scale experiments conducted in a 50 m x 50 m wave basin involving five idealised calving mechanisms. The icebergs were modelled with blocks and resistance type wave probes were used to record the water surface elevations. The experimental data were post-processed to improve their quality and exclude the physically meaningless information, such as noise and the reflected waves from the basin walls. The relevant wave features were hence extracted from the post-processed measurements, including the maximum wave height, amplitude and the corresponding period. The largest waves were observed in the experiments where the iceberg calving was dominated by the gravity force whereas the calving mechanisms dominated by the buoyancy force generated approximately an order of magnitude smaller waves. The maximum wave height, amplitude, the corresponding wave period and their decay were expressed as a function of six governing dimensionless parameters, including the relative released energy Er, Froude number F, relative iceberg thickness S, relative iceberg width B, relative iceberg volume V and the relative density D. These equations were derived and validated relatively well for each of the five calving mechanisms ...